Tekanan Waktu, Beban Kerja, Dan Stres Kerja Pada Work Life Balance Wanita Karir - Yuliastri, Rika Maulidya; Qurochman, Arief Nurdiannova (Jurnal E-Bis, 2024)
Career women are often faced with matters related to balancing their personal life with their work. This research focuses on determining the role of time pressure, workload, and work stress on work life balance in career women. The sample for this research was 36 career women in Kendalsari Rungkut, Surabaya. This research utilizes quantitative methods with multiple linear regression. According to the results of the F test, the results obtained a significance level exceeding 0.05, which shows that all dependent variables do not play a comprehensive role in work life balance. The magnitude of the role of the three independent variables in work life balance is 21.3%, while the rest is caused by other things. According to the t test results, time pressure and workload do not play a role in work life balance, while work stress plays a role in work life balance.